Protein O-mannosylation is crucial for human mesencyhmal stem cells fate - Ragni, Enrico; Lommel, Mark; Strahl, Sabine (Cellular and molecular life sciences, 2015)
Human mesenchymal stem cells (MSC) are promising cell types in the field of regenerative medicine. Although many pathways have been dissected in the effort to better understand and characterize MSC potential, the impact of protein N- or O-glycosylation has been neglected. Deficient protein O-mannosylation is a pathomechanism underlying severe congenital muscular dystrophies (CMD) that start to develop at the embryonic developmental stage and progress in the adult, often in tissues where MSC exert their function. Here we show that O-mannosylation genes, many of which are putative or verified glycosyltransferases (GTs), are expressed in a similar pattern in MSC from adipose tissue, bone marrow, and umbilical cord blood and that their expression levels are retained constant during mesengenic differentiation. Inhibition of the first players of the enzymatic cascade, POMT1/2, resulted in complete abolishment of chondrogenesis and alterations of adipogenic and osteogenic potential together with a lethal effect during myogenic induction. Since to date, no therapy for CMD is available, we explored the possibility of using MSC extracellular vesicles (EVs) as molecular source of functional GTs mRNA. All MSC secrete POMT1 mRNA-containing EVs that are able to efficiently fuse with myoblasts which are among the most affected cells by CMD. Intriguingly, in a pomt1 patient myoblast line EVs were able to partially revert O-mannosylation deficiency and contribute to a morphology recovery. Altogether, these results emphasize the crucial role of protein O-mannosylation in stem cell fate and properties and open the possibility of using MSC vesicles as a novel therapeutic approach to CMD.